IMPROVEMENT OF METHODS OF DETECTION AND DRUG THERAPY OF CHRONIC PHARYNGEAL INFLAMMATION IN CONCOMITANT CHRONIC TONSILLITIS (World Bulletin of Public Health, 2025)
Chronic inflammatory diseases of the pharynx and palatine tonsils are one of the most common and socially significant problems of modern otorhinolaryngology. According to the World Health Organization, chronic pharyngitis is diagnosed in 10-15% of the adult population of developed countries, while in 60-70% of cases it is combined with chronic tonsillitis, which significantly complicates the diagnosis, treatment and prognosis of the disease
Keywords: Chronic pharyngitis; chronic tonsillitis; therapeutic approaches